The Unfinished Nature of Women’s Leadership in Higher Education - DeLaquil, Tessa (International Higher Education, 2021)
Development in gender equality in higher education is not uniform, especially lagging in positions of leadership and decision-making. It may be considered as “unfinished” or “partial” at national/regional, historical and sociocultural, and individual levels, and thus requires concerted efforts to provide support at each level.